Glonass Russian Technologies Methods of Use Of Era-Glonass in Ground Monitoring. (Eurasian Scientific Herald, 2023)
With the development of our republic, suyuyol will use the system of the year and the requirements for monitoring agricultural production will increase. including glonass Russian technologies It is expedient to study and apply methods of using era-glonass on the earth monitor and apply in our region.